SELECTIVITY OF THE HERBICIDE DICAMBA (XTENDICAM) APPLIED AT THE TILLERING STAGE OF WHEAT - Cagnini, Sttéfani Vitória Zago; de Moraes, Pedro Valério Dutra; Russiano, Maira Cristina Schuster; Morgan, Samara Baú; Pagnussat, Joana Lucia; Negri, Vitor; Rossi, Patricia; Machado, André Bressiani (Seven Editora, 2026)
The use of hormonal herbicides in wheat requires evaluation regarding selectivity, especially for molecules without registered recommendations for this crop. This study aimed to evaluate the effect of different doses of dicamba (Xtendicam) applied at the tillering stage of wheat on phytotoxicity and yield components. The experiment was conducted under field conditions in Verê, Paraná, Brazil, using a randomized complete block design with four replications and five treatments (0; 0.4; 0.6; 0.8; and 1 L ha⁻¹). The evaluated variables included phytotoxicity, plant height, number of tillers, number of grains per spike, thousand-grain weight, dry biomass, and yield. Increasing doses resulted in higher phytotoxicity, reaching 15.5% at 42 days after application at the highest dose, which was considered low and reversible. Reductions were observed in plant height, number of tillers, and number of grains per spike at higher doses. Grain yield was reduced at all doses, with a significant difference at 0.8 L ha⁻¹, showing a reduction of up to 34.9% compared to the control. The number of plants per linear meter, dry biomass, and thousand-grain weight were not affected. The results indicate that, although visual phytotoxicity was low, dicamba negatively affects wheat yield components. The dose of 0.4 L ha⁻¹ showed the lowest impact on the crop and was considered the safest under the evaluated conditions.